Keratoconus and inflammatory bowel disease: mendelian randomization - Jin, Yiheng; Wang, Yuanfeng; Qiu, Xu; Liu, Jiao; Qu, Shugen (Frontiers in Genetics, 2024)
Background Keratoconus is a diseased corneal dilation of unknown etiology.Studies have shown that inflammation may play a role in keratoconus. Inflammatory enteritis (IBD), including ulcerative colitis(UC), is a chronic, systemic inflammatory disease. We used Mendelian randomization to assess the causal relationship among IBD, UC and keratoconus. Methods The instrumental variable of IBD and UC was selected, the information of the instrumental variable in keratoconus outcome was extracted, and the causal relationship was assessed by the inverse variance weighted method by primary analysis, and its relevant sensitivity analysis. Results A causal relationship between IBD and keratoconus was observed significantly (P=0.017, OR=1.21, 95%CI=1.03-1.41), and same as to UC and keratoconus (P=0.038, OR=1.25, 95%CI=1.01-1.54). Conclusion IBD may play a causal role in the development of keratoconus, but the mechanism needs to be further elucidated.